The Influence Of Product Diversification, Service Quality, Price, Lifestyle, And Product Knowledge On Consumer Purchase Decisions : Financial Perspectives From The Electronics Retail Sector - Bayu Wijayantini; Tegar Laksamana Wahyudi; Retno Endah Supeni (MINOVa Ditria Jaya, 2025)
In an era of intense business competition, understanding the determinants of consumer purchase decisions is crucial, particularly in the electronics retail sector. This study investigates the impact of product diversification, service quality, price, lifestyle, and product knowledge on consumer purchase decisions from a financial perspective. Focusing on TG Electronics Store in Ambulu, Jember Regency, this research employs a quantitative survey approach, gathering responses from 190 consumers. The collected data were analyzed using multiple linear regression to examine the relationships between independent variables and purchasing decisions. The findings reveal that product diversification positively and significantly influences consumer purchase decisions, highlighting the importance of offering a wide range of products to meet diverse consumer needs. Price also demonstrates a significant impact, reinforcing the role of competitive pricing strategies in shaping consumer behavior. Likewise, lifestyle and product knowledge are found to significantly affect purchasing decisions, suggesting that consumer preferences and awareness of electronic products play a vital role in the decision-making process. However, service quality does not exhibit a significant effect, indicating that other factors may take precedence in consumer considerations when purchasing electronics. These insights offer valuable implications for TG Electronics Store and similar retailers, emphasizing the need for strategic product diversification, competitive pricing, and enhanced consumer education to drive sales. This study contributes to the literature on consumer purchasing behavior by integrating financial perspectives into the analysis, providing a contemporary understanding of market dynamics in the electronics retail sector.